Sedimentary fabric characterized by X‐ray tomography: A case‐study from tsunami deposits on the Marquesas Islands, French Polynesia. Issue 3 (28th March 2019) - Paris, Raphaël; Falvard, Simon; Chagué, Catherine; Goff, James; Etienne, Samuel; Doumalin, Pascal
Abstract: X‐ray tomography is used to analyse the grain size and sedimentary fabric of two tsunami deposits in the Marquesas Islands (French Polynesia, Pacific Ocean) which are particularly exposed to trans‐Pacific tsunamis. One site is located on the southern coast of Nuku Hiva Island (Hooumi) and the other one is on the southern coast of Hiva Oa Island (Tahauku). Results are compared with other techniques such as two‐dimensional image analysis on bulk samples (particle analyser) and anisotropy of magnetic susceptibility. The sedimentary fabric is characterized through three‐dimensional stacks of horizontal slices (following a vertical step of 2·5 mm along the cores), while grain‐size distribution is estimated from two‐dimensional vertical slices (following a step of 2 mm). Four types of fabric are distinguished: (a) moderate to high angle (15 to 75°); (b) bimodal low‐angle (<15°); (c) low to high angle with at least two different orientations; and (d) dispersed fabric. The fabric geometry in a tsunami deposit is not only controlled by the characteristics of the flow itself (current strength, flow regime, etc.) but also sediment concentration, deposition rate and grain‐size distribution. There is a notable correlation between unimodal high‐angle fabric – type (a) – and finely‐skewed grain‐size distribution. The two tsunami deposits studied represent two different scenarios of inundation. As demonstrated here, X‐ray tomography is an essential method for characterizing past tsunamis from their deposits. The method can be applied to many other types of sediments and sedimentary rocks.